Inglês instrumental, inglês para negócios e inglês instrumental para negócios - Vian Jr, Orlando (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This article aims, from a broader perspective, at (1) discussing some definitions of English for Specific Purposes currently used by theorists and practiotiners in the area, focusing on the implications, causes and consequences brought about by these studies, trying then to define, (2) what English for General Business Purposes is as well as its implications for teaching English in-companies and, from a narrower perspective, discuss what English for Sp